(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
This article presents the results of studying the characteristics of aging the garden roses under introduction. The study of the ontogeny of the roses planted to aging found that the hybrid tea, grandiflora and floribunda cultivars are able to resume 40–48 growth of shoots. Then ageing of plants starts, which greatly reduces their regenerative ability, ornamental and productive qualities. On the roots of a large part of the 11–17-уear-olds bushes tumor was formed. It is the result of reducing of the resistance of the aging organism to bacterial, viral and fungal diseases. Tumor on ageing roses roots, indefinitely increasing in size as a result of the pathological dividing cumbium, gradually causing irreversible disturbance of the vital functions of plant organism and eventually lead to their death.